TRANSDISCIPLlNINIS PROJEKTAS: PROVERŽIS Į MOKSLŲ IR PRAKTIKOS SINTEZĘ? - Kanišauskas, Saulius (Problems / Problemos, 2011)
The second half of the 20th century witnessed discontent with rigid distinction between science specializations, thus science integration processes which can be described in terms of multi, poli, pliurali, inter, transdisciplinary started to evolve. The article attempts to show that the international term "discipline" has a significantly broader meaning than the Lithuanian term "subject", which is perceived as a branch or field of science. It is maintained that the vulnerability degree of "disciplinary purity" should be the most important criterion which allows defining relation types of disciplines. However, conversely to other types of disciplinary integration, the transdisciplinary project rejects the requirement of "disciplinary purity" in principle. Moreover, the transdisciplinary project is first associated with striving to direct the academic science that it could satisfy the pragmatic social needs through introduction of non-academic factors. Also, the article points out that the "strong version" of the transdiciplinary project which focuses on the need to delve into fundamental questions of worldview and which attempts to consolidate all sciences faces serious ontological and epistemological problems. As a result, there is considerable danger that due to not solved epistemological problems, the transdisciplinary project is at risk to remain of apologetic character and a source of heuristics.